ANALYSIS OF STUNTING INCIDENTS IN TODDLER CHILDREN AT THE SERI TANJUNG COMMUNITY HEALTH CENTER, OGAN ILIR - Juniana; Ali Harokan; Akhmad Dwi Priyatno (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2024)
Stunting is a condition of failure to thrive in children under five years old. In 2023, there will still be 45 stunting cases and 52 underweight toddlers. This study aims to determine the factors associated with the incidence of stunting in children under five at the Seri Tanjung Community Health Center, Ogan Ilir Regency in 2024. The design of this research is quantitative with a cross-sectional approach.  The population of this study were parents of children under five who were seeking treatment at the Seri Tanjung Community Health Center in 2024. The sample in this study was 95 people. The sampling method uses purposive sampling. This research was carried out on 10 -20 February 2024. Data was collected using a questionnaire. Bivariate data analysis used the Chi-Square test and multivariate logistic regression. The results of the research show that there is a relationship between age (p value 0.040), exclusive breastfeeding (p value 0.002) and LBW (p value 0.047) with the incidence of stunting in children under five at the Seri Tanjung Community Health Center in 2024. There is no relationship between gender (p value 0.075), employment (p value 0.12) and income (p value 0.823) with the incidence of stunting in children under five at the Seri Tanjung Community Health Center in 2024. The most dominant factor with the incidence of stunting in children under five at the Seri Tanjung Community Health Center in 2024 is exclusive breast milk (OR 0.210 ), if you don't provide exclusive breast milk, you have a 0.210 times risk of stunting compared to giving exclusive breast milk. The conclusion is that there is a relationship between age, exclusive breastfeeding and LBW. Community health centers need to provide counseling every two months in an effort to increase parents' knowledge of stunting and provide counseling guidance to parents regarding knowledge of exclusive breastfeeding.